Decadal Variability in the South Pacific Subtropical Countercurrent and Regional Mesoscale Eddy Activity - Travis, Seth; Qiu, Bo (Journal of physical oceanography, 2017)
Decadal variability of eddy activity in the western, subtropical South Pacific is examined using the past two decades of satellite altimetry data. Between 21° and 29°S, there is a band of heightened eddy activity. In this region, the eastward South Pacific Subtropical Countercurrent (STCC) overlays the westward South Equatorial Current (SEC). This vertically sheared STCC–SEC system is subject to baroclinic instabilities. By using the European Centre for Medium-Range Weather Forecasts (ECMWF) Ocean Reanalysis System, version 4 (ORAS4), data and verifying with the gridded Argo float data, low-frequency variations in the state of the ocean in this region are investigated. It is found that the low-frequency changes in the shearing and stratification of the STCC–SEC region simultaneously work to modulate the strength of baroclinic instabilities, as measured through the baroclinic growth rate. These changes in the strength of the instabilities consequently affect the observed eddy activity. Using a linearization of the baroclinic growth rate, the contribution to the variability from the changes in shearing is found to be roughly twice as large as those from changes in stratification. Additionally, changes in the temperature and salinity fields are both found to have significant impacts on the low-frequency variability of shearing and stratification, for which salinity changes are responsible for 50%–75% of the variability as caused by temperature changes. However, the changes in all these parameters do not occur concurrently and can alternately work to negate or augment each other.